Porcine models for the study of small‐for‐size syndrome and portal inflow modulation: literature review and proposal for a standardized nomenclature. (6th October 2016) - Mohkam, Kayvan; Darnis, Benjamin; Mabrut, Jean‐Yves
Abstract: Porcine models of extended hepatectomy and liver transplantation (LT) of reduced graft have been widely used for studying the small‐for‐size (SFS) syndrome and the various modalities of portal inflow modulation (PIM). However, considerable heterogeneity exists among the studies and their results. The aim of this review was to assess the main advantages and drawbacks of the different porcine models of SFS LT and SFS hepatectomy, and propose a standardized anatomical nomenclature for the various models. The MEDLINE database was searched for articles reporting porcine models of reduced graft LT or hepatectomy of more than 65%. Nineteen articles on SFS LT matched our inclusion criteria, including 10 articles reporting a model of PIM. Twenty‐seven articles reporting a model of posthepatectomy SFS were identified, of which 16 reported a model of PIM. Subtotal hepatectomy (i.e. resection of all segments except segment 1) without inflow occlusion, left trisectionectomy with inflow occlusion, and LT of a right lateral section including the caudate lobe in a larger recipient appeared to be the most suitable porcine models for studying the SFS syndrome. All three models were appropriate for assessing the surgical and pharmaceutical PIM modalities, except for those involving the splenic flow. Abstract : Mohkam and colleagues reviewed the various existing porcine models of small‐for‐size liver transplantation or partial hepatectomy and portal inflow modulation. They proposed a standardized nomenclature for these models and identified subtotal hepatectomy, left trisectionectomy with inflow occlusion and liver transplantation of the right lateral section as the most appropriate models.